Emulsified sausages obtained from mechanically separated meat of yacare caiman (Caiman yacare) - CAVENAGHI-ALTEMIO, Angela Dulce; SANTIAGO, Lara Liss Silva; FIGUEIREDO, Wellington Vargas; FONSECA, Gustavo Graciano (Food Science and Technology, 2024)
This study aimed at the development and characterization of emulsified sausages using mechanically separated meat (MSM) from yacare caiman (Caiman yacare). The sausages were formulated using three different treatments containing (in %) 70.0 (T1), 75.0 (T2), or 80.0 (T3) of MSM of yacare and subjected to comprehensive analyses, including chemical composition, physical properties, microbiological safety, and sensory attributes. The proximate composition analysis revealed that moisture was the unique parameter that presented statistical differences between treatments, ranging from 74.94% (T1) to 72.35% (T3). pH and water activity measurements indicated stable and safe products, with high water activity attributed to water incorporation during emulsion formation. Color differences were observed among treatments, potentially linked to formulation, especially the MSM content. The highest average obtained for luminosity was 49.87 for T2, differing statistically (P > 0.05) from T1 and T3. Consistent shear force values suggested effective emulsion formation and processing. The microbiological analysis demonstrated the safety of sausages, meeting microbial standards for consumption. Sensory evaluation revealed positive responses to appearance and aroma, while flavor and texture received mixed reviews. Purchase intention scores indicated cautious consumer interest. Thus, further efforts are needed to optimize formulations and processing to enhance consumer sensory attributes to meet consumer preferences and improve acceptance, achieve marketability, and capitalize on the ecological and nutritional benefits of yacare caiman-derived products.